Complements to Level 2 surf-riding/broaching vulnerability criterion regarding waterjet propelled ships and wave surge force correction. (15th March 2023) - Feng, Peiyuan; Cai, Youlin; Zhou, Yaohua; Fan, Sheming; Ma, Ning
Abstract: The Second Generation Intact Stability Criteria (SGISC) has officially entered the trial period for further validations and to collect feedback based on applications. This study focuses on the Level 2 surf-riding/broaching vulnerability criterion and proposes complements to the assessment procedures regarding two important issues. One is that the current procedure is only applicable to ships using propellers. However, waterjet propelled ships are common nowadays and they may be vulnerable to this stability failure mode as well. The other issue is that there lacks a both reliable and practical method for the wave surge force correction. The current procedure uses the Froude-Krylov (FK) component of the first order wave surge force as the input for the assessment, which significantly over-estimates the probability of surf-riding occurrence. Through the introduction of the thrust coefficient K T and the advance coefficient J for waterjet systems, the first issue is addressed by model the waterjet thrust based on the K T ∼ J relationship just as that of propellers. The validity of such treatment is first demonstrated through the actual data of a real pump, while the rationale behind the universality of such modelling is analyzed based on dimensional analysis. The second issue is addressed through the proposal of a practical method to estimate the wave surge force correction factor based on the ratio between the first order wave surge force and its FK component. Sample ship calculations are performed to demonstrate the reliability of the proposed method. Finally, the complete Level 2 surf-riding/broaching vulnerability assessment for a waterjet propelled ship is performed for demonstration. This study contributes to the improvement of SGISC, making it applicable to a wider range of ship types with higher accuracy. Highlights: A practical method to model the waterjet thrust characteristics is established. Validity of the waterjet thrust model is demonstrated based on the dimensional analysis method. Level 2 assessment procedures for waterjet propelled ships are proposed with minimal modifications to the existing ones. A new method to estimate the correction factor for wave surge force is proposed. A waterjet propelled sample ship is used to demonstrate the complete assessment procedures.